Comparison of two viscoelastic testing devices in a porcine model of surgery, hemorrhage and resuscitation - Gruneberg, Daniel; Dietrich, Maximilian; Studier-Fischer, Alexander; Petersen, Clara; von der Forst, Maik; Özdemir, Berkin; Schöchl, Herbert; Nickel, Felix; Weigand, Markus A.; Schmitt, Felix C. F. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Viscoelastic hemostatic assays (VHA) are integral in contemporary hemostatic resuscitation, offering insights into clot formation, firmness, and lysis for rapid diagnosis and targeted therapy. Large animal models, particularly swine, provide anatomical and physiological analogies for coagulation research. Despite the growing use of VHAs, the ClotPro ® device's applicability in porcine models remains unexplored. This study investigates ClotPro ® in a porcine model of abdominal surgery, severe hemorrhage, and resuscitation, comparing it with the established ROTEM ® delta system. Methods: Twenty-seven healthy pigs underwent abdominal surgery, hemorrhage and resuscitation. ClotPro ® and ROTEM ® were used to assess viscoelastic hemostatic properties at baseline, after surgery, 60min after shock induction, 60min and 120min after resuscitation.Results: Clotting times in extrinsically and intrinsically stimulated assays exhibited fair to moderate correlation. Clot firmness in extrinsically stimulated tests could be used interchangeably while fibrin polymerization assays revealed significant differences between the devices. Fibrin polymerization assays in ClotPro ® consistently yielded higher values than ROTEM ® . Furthermore, the study evaluated the ClotPro ® TPA-test's applicability in porcine blood, revealing failure of lysis induction in porcine blood samples. Conclusion: This research contributes valuable insights into the use of ClotPro ® in porcine models of hemorrhage and coagulopathy, highlighting both its applicability and limitations in comparison to ROTEM ® delta. The observed differences, especially in fibrin polymerization assays, emphasize the importance of understanding device-specific characteristics when interpreting results. Due to its inapplicability, TPA-test should not be used in porcine blood to evaluate fibrinolytic potential. The study provides a foundation for future investigations into the use of different viscoelastic hemostatic assays in porcine animal models.